Crizotinib inhibits activation of MET pathway caused by MET extracellular SEMA domain duplication. (September 2020) - Lin, Jiatong; Lyu, Yingcheng; Li, Lin; Wu, Duoguang; Chen, Jiewen; Lin, Tengjiao; Huang, Zhan; Hu, Jinwei; Wang, Wenjing; Lin, Huayue; Wang, Minghui
Highlights: A novel MET SEMA domain duplication was identified in a non-small cell lung cancer patient. Off-label use of the kinase inhibitor crizotinib led to a marked response of the patient. Cellular analyses provide a functional basis for the oncogenic role of the structural MET alteration. The novel MET mutation may represent actionable targets in lung cancer patients. Abstract: Objective: Aberrant MET activation, which promotes cell proliferation and tumor metastasis, occurs in many types of cancer and results from multiple mechanisms. A novel MET duplication mutation was found in a non-small cell lung cancer (NSCLC) patient. The clinical response to crizotinib was investigated and the functional relevance was characterized in cellular models. Materials and Methods: Next-generation sequencing (NGS) was performed on the tumor tissue and circulating tumor DNA (ctDNA) of a patient with advanced NSCLC. In vitro studies including western blot, proliferation assays and colony formation assays were used to confirm the clinical observations. Results: The patient was identified to harbor a duplication of the MET SEMA domain. After a month of treatment, the patient showed a marked response to crizotinib, a multikinase inhibitor with potent activity against MET. Functional in vitro studies demonstrated that expression of MET SEMA duplication in NIH-3T3 cells stimulated the activation of MET signaling. Crizotinib treatment obviously repressed cell proliferation, colony formation, and MET signaling pathway. Conclusion: Crizotinib treatment resulted in a clinical response in a patient with MET SEMA duplication. Results of cellular analyses together with the clinical data suggest that this novel alteration may represent an actionable target in NSCLC patients.